Perempuan Penjual Ikan Junjung Keliling di Kota Kendari - Idrawan, Idrawan; Sifatu, Wa Ode; Raemon, Raemon (JURNAL KABANTI: Kerabat Antropologi, 2024)
The objective of this study is to gain insight into the challenges that female traveling junjung fish vendors encounter while selling fish and strategize solutions for resolving these issues while also assisting with household chores. This study interprets the data through the lens of Carol Steack's (1974) perspective on social organizations. The present study employs observation, in-depth interviews, and documentation as methods of data collection. The findings of this study indicate that women engaged in the trade of junjung fish in Gunung Jati Village fulfill their domestic responsibilities while performing their labor, which consists of selling fish. As a result, these women are capable of providing economic assistance to their families. Female vendors of junjung fish encounter challenges such as purchasers seeking to borrow funds and weariness from arduous mountain ascending. In order to address this issue, the women who sell junjung fish in Gunung Jati Village have devised a strategy: in the event that they experience fatigue while ascending the mountain, they will pause for an estimated duration of one to five minutes along the side of the road to refuel. Additionally, they have devised a method to appease customers who persistently seek financial assistance: persuade purchasers that if the junjung fish vendors consent to indebtedness on their fish, they will receive a refund